Dramatic Response to Pramipexole in Delayed-Onset Parkinsonism from Osmotic Demyelinating Syndrome. (16th June 2020) - Han, Steve C.; Katus, Linn; Frucht, Steven
Background: Delayed parkinsonism and dystonia are recognized phenomena in osmotic demyelinating syndrome (ODS). Dopamine receptor agonists and levodopa have been reported to benefit select patients. Case report: We report a patient with ODS with severe pseudobulbar deficits, parkinsonism and dystonia, poorly responsive to levodopa, who experienced a remarkable improvement with pramipexole. Discussion: A marked response to pramipexole with lack of response to levodopa suggests a pre-synaptic source for his deficits coupled with injuries to non-nigral compensatory structures. Highlights: This case highlights a dramatic response of osmotic demyelination-induced parkinsonism/dystonia to pramipexole. A lack of response to levodopa suggests deficits in the pre-synaptic nigral as well as non-nigral compensatory structures.